Emotional cherry picking: the role of personality and goal orientation in selective emotion regulation for musical practice - Breaden Madden, Gerard; Herff, Steffen A.; Beveridge, Scott; Jabusch, Hans-Christian (Frontiers in Psychology, 2023)
Introduction: Emotion regulation is an important part of optimising performance and successful goal pursuit in practice-based tasks such as making music. Musicians may regulate their own emotions during the course of their musical practice in order to improve their performance and ultimately attain their practice-related goals. The specific emotions they target may depend upon their personality traits but may also relate to the nature of their goal orientation, and the interaction between the two. In addition, when pursing a complex or demanding goal, musicians may desire emotions which are consistent with the quality of a personality trait. This study investigates whether the emotions desired by musicians during their musical practice were dependent on their personality traits and Mastery goal orientation (the desire to master musical and technical skills). Methods: Via an online questionnaire, 421 musicians completed a personality scale and answered questions relating to their mastery practice goals. They also completed an emotion scale indicating how strongly they desired to increase or decrease the intensity of emotions when practicing. Results: Overall, musicians preferred to up-regulate positive over negative emotions (paired t(420) = 58.13, p < .001). Using Bayesian Mixed Effects models, we found evidence that personality traits affected the desire to regulate specific emotions. For example, higher levels of Agreeableness predicted greater desire to increase positive but not negative emotions. Extraversion on the other hand, predicted greater desire to increase anger (Est = .05, SE = .03, Odds(Est>0) = 43.03) but not pleasant emotions. Findings confirm a general hedonic principle underlying the emotions that musicians desire for their musical practice. However, predicted by personality traits, musicians also sometimes sought to increase the intensity of unpleasant emotions. Discussion: These findings complement existing research that suggests that some Mastery-oriented musicians may seek an emotional state consisting of both positive and negative emotions. This and future studies on this topic may contribute to a better understanding of individual differences in emotion regulation ability as a potential aspect of individualized musical practice strategies.